Impact of COVID-19 on tuberculosis notifications - Pontes, Talita Antunes Antoniolli (2024)
The COVID-19 pandemic has significantly impacted the control of diseases by overwhelming healthcare systems, and tuberculosis (TB) notifications may have been affected. This study aimed to analyze the impact of COVID-19 on TB notifications in the Sao Paulo State. This is a retrospective study examining TB notifications extracted from the TBweb database (Jan 2015 to Dec 2022). We conducted an interrupted time series (ITS) analysis of TB notifications using the declaration of the COVID-19 pandemic as the interrupting event (Bayesian causal impact analysis). A total of 177,103 notifications of TB incident cases were analyzed, revealing a significant decrease in 2020 (13%) and in 2021 (9%), which lost significance in 2022. However, changes were not associated with population density or the area of the regions. Future analyses of the effects of TB underdiagnosis might help describe the impact of underreporting on future TB incidence and mortality.